2016
DOI: 10.13057/biodiv/d170258
|View full text |Cite
|
Sign up to set email alerts
|

The length-weight correlation and population dynamics of razor clams (Solen regularis) in Surabaya east coast, Indonesia

Abstract: Abstract. Trisyani N, Herawati EY, Widodo MS, Setyohadi D. 2016. The length-weight correlation and population dynamics of razor clams (Solen regularis) in Surabaya east coast,. Solen regularis is a pelecypod species living in intertidal areas at sandy substrate. In Surabaya east coast, Solen regularis is exploited by the locals for consumption, both as fresh seafood or processed one. This research aims to analyze the length-weight correlation of the clams and the population dynamics, conducted from August 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
1
0
4
Order By: Relevance
“…Nguồn cung cấp thức ăn trên nền cát ở vùng bãi triều tương đối thấp, phụ thuộc vào các dòng suối mang phiêu sinh vật vì móng tay là sinh vật đáy và ăn thức ăn lơ lửng. Khả năng thích nghi với hình dạng cơ thể thuôn dài ở các vùng bãi triều có nhiều cát cho phép móng tay đào nhanh hơn ngay khi sóng đi qua để nâng cơ thể lên trên bề mặt (Trisyani et al, 2016). Thông thường, móng tay có thân hình mảnh mai, nhỏ với các bộ phận được tiến hóa phù hợp với mục đích đào nhanh hơn (Trisyani et al, 2016).…”
Section: Tương Quan Các Chiều Kích Thước Của Móng Tay Tại Vqg Xuân Thủyunclassified
See 3 more Smart Citations
“…Nguồn cung cấp thức ăn trên nền cát ở vùng bãi triều tương đối thấp, phụ thuộc vào các dòng suối mang phiêu sinh vật vì móng tay là sinh vật đáy và ăn thức ăn lơ lửng. Khả năng thích nghi với hình dạng cơ thể thuôn dài ở các vùng bãi triều có nhiều cát cho phép móng tay đào nhanh hơn ngay khi sóng đi qua để nâng cơ thể lên trên bề mặt (Trisyani et al, 2016). Thông thường, móng tay có thân hình mảnh mai, nhỏ với các bộ phận được tiến hóa phù hợp với mục đích đào nhanh hơn (Trisyani et al, 2016).…”
Section: Tương Quan Các Chiều Kích Thước Của Móng Tay Tại Vqg Xuân Thủyunclassified
“…Khả năng thích nghi với hình dạng cơ thể thuôn dài ở các vùng bãi triều có nhiều cát cho phép móng tay đào nhanh hơn ngay khi sóng đi qua để nâng cơ thể lên trên bề mặt (Trisyani et al, 2016). Thông thường, móng tay có thân hình mảnh mai, nhỏ với các bộ phận được tiến hóa phù hợp với mục đích đào nhanh hơn (Trisyani et al, 2016). Mối tương quan chiều dài -khối lượng toàn thân (Hình 4) cho thấy móng tay ở VQG Xuân thủy có hệ số b < 3.…”
Section: Tương Quan Các Chiều Kích Thước Của Móng Tay Tại Vqg Xuân Thủyunclassified
See 2 more Smart Citations
“…was important to evaluate the actual genetic consequences (Yoon 2018). The COI has been used to confirm the phylogenetic relationship between Solen spp., which is located on the east coast of Surabaya and Pamekasan beach (Trisyani et al 2016a). The results showed that Solen spp.…”
Section: Introductionmentioning
confidence: 97%